2014
DOI: 10.1111/jpn.12232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and zinc supplementation on transport properties in the jejunum of piglets

Abstract: Zinc is effective in the prevention and treatment of post-weaning diarrhoea and in promoting piglet growth. Its effects on the absorption of nutrients and the secretory capacity of the intestinal epithelium are controversial. We investigated the effects of age, dietary pharmacological zinc supplementation and acute zinc exposure in vitro on small-intestinal transport properties of weaned piglets. We further examined whether the effect of zinc on secretory responses depended on the pathway by which chloride sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Nevertheless, the amounts of Zn consumed often exceed well-established nutritional requirements ( 7 9 ). Recent studies reported that Zn overdose exposure can have deleterious consequences, such as decreasing immune function, altering intestinal absorptive and secretory capacity, or increasing visceral adiposity ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the amounts of Zn consumed often exceed well-established nutritional requirements ( 7 9 ). Recent studies reported that Zn overdose exposure can have deleterious consequences, such as decreasing immune function, altering intestinal absorptive and secretory capacity, or increasing visceral adiposity ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of fluid movement through the small intestine epithelium is of physiological interest and clinical relevance. We selected zinc as a candidate inhibitor of fluid flow because of its purported antidiarrheal properties [ 22 , 23 , 24 , 25 , 26 ] and influence on epithelial tight junction integrity and ion secretion [ 27 , 28 , 29 , 30 , 31 ]. Fluid flow by cultured enterocytes exposed to vigorous aeration was first measured for 5 min without zinc to obtain a baseline rate of flow.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the results showed that CS–Zn or ZnSO 4 both increased the expression of zinc transporter protein, and the expression of zinc transporter protein increased linearly with supplemental zinc. ZnT1 is distributed on the basolateral membrane of enterocytes; the function of ZnT1 is to transport excess intestinal zinc into extracellular matrix or organelles for the sake of reducing the zinc level of cytoplasm [ 25 ]. Increased zinc concentrations significantly elevated intestinal ZnT1 mRNA and protein expression [ 26 ].…”
Section: Resultsmentioning
confidence: 99%